Advances in Ecological Speciation: an integrative approach. Issue 3 (February 2014) - Faria, Rui; Renaut, Sebastien; Galindo, Juan; Pinho, Catarina; Melo‐Ferreira, José; Melo, Martim; Jones, Felicity; Salzburger, Walter; Schluter, Dolph; Butlin, Roger
<x xml:space="preserve">Abstract</x> The role of natural selection in promoting reproductive isolation has received substantial renewed interest within the last two decades. As a consequence, the study of ecological speciation has become an extremely productive research area in modern evolutionary biology. Recent innovations in sequencing technologies offer an unprecedented opportunity to study the mechanisms involved in ecological speciation. Genome scans provide significant insights but have some important limitations; efforts are needed to integrate them with other approaches to make full use of the sequencing data deluge. An international conference 'Advances in Ecological Speciation' organized by the University of Porto (Portugal) aimed to review current progress in ecological speciation. Using some of the examples presented at the conference, we highlight the benefits of integrating ecological and genomic data and discuss different mechanisms of parallel evolution. Finally, future avenues of research are suggested to advance our knowledge concerning the role of natural selection in the establishment of reproductive isolation during ecological speciation.